Avrupa Parlamentosu'nda Avrupa şüpheciliği : krizler ve etkileri - Karahan, Gizem (My University, 2020)
İkinci Dünya Savaşı’ndan sonra Avrupa’da barışın ve istikrarın yeniden sağlanması amacıyla tasarlanan Avrupa Birliği projesi ortaya çıktığı günden beri tartışmaları gündeme getirmiştir. Avrupa Birliği’ni destekleyen görüşler olduğu kadar Avrupa Birliği’nin kurumlarını, politikalarını eleştiren veya tamamen bütünleşme sürecine karşı çıkan görüşler de olmuştur. 1990’lı yılların başında Avrupa gündeminde önemli bir hale geldiği kabul edilen eleştirel görüşler literatürde Avrupa şüpheciliği (Euroscepticism) olarak adlandırılmıştır. Zaman zaman gündeme gelen Avrupa şüpheciliği geçtiğimiz son on yılda Avrupa Birliği’nin karşılaştığı birçok krizle tekrar ortaya çıkmıştır. Avrupa şüpheciliğinde ulusal ve ulusüstü düzeyde olmak üzere belirgin bir artış görülmüştür. Bu tez çalışmasında, krizlerin Avrupa Parlamentosu’nda güçlenen şüpheci siyasi gruplar ile etkileşiminin Avrupa politikalarına etkisi sorgulanmaktadır.

The European Union project, which was designed to restore peace and stability in Europe after the Second World War, has brought to discussions on the agenda since the day it emerged. There have been opinions that support the European Union as well as criticize the institutions and policies of the European Union or oppose the integration process completely. Critical views that are accepted to have become important in the European agenda in the early 1990s have been named as Euroscepticism in the literature. Euroscepticism, which has come to the fore from time to time, has reemerged as a result of crises in the last decade. There has been a marked increase in Euroscepticism at the national and supranational level. In this thesis, the effects of the interaction of crises with Eurosceptic political groups that have gained strength in the European Parliament on European policies are questioned.
Keywords: Avrupa Birliği; Avrupa Parlamentosu; Avrupa Şüpheciliği; Brexit; Brexit Euroscepticism; Euro Crisis; Euro Krizi; European Parliament; European Union; Göç Krizi; Migration Crisis; Political science; Siyasal bilim